Anne Brontë and Scarborough. (2nd January 2022) - Chitham, Edward
Abstract : It has been claimed that Anne Brontë could know little about the gentry and aristocracy since her experience was so limited. This essay shows that this was far from the case. Her life in five summers with the Robinsons has been called 'a visit', but altogether she spent a total of twenty-five weeks at Scarborough, almost half a year. During this time she met and observed the varied life of a busy town and its visitors, learning about the lives of a wide range of people. We are able to discover from the lists published in Scarborough newspapers the names of many of her neighbours, in some cases living in the same apartments. The row which has been called 'Wood's Lodgings' was in fact shared between William Wood and Dr William Wilson. The row opposite was also, in the main, high-quality lodgings. Anne could observe their occupants as well. Some of the visitors she may have known, but others she had not previously met would have an influence on her writing.